Basement Membrane Changes of Myofiber and Fibrosis in Sternocleidomastoid Muscle of Congenital Muscular Torticollis. Issue 8 (2nd November 2022) - Gao, Futang; Zeng, Shuaidan; Tang, Shengping; Ning, Pei; Qiu, Xin; Cai, Ting; Tang, Gen; Xiong, Zhu
Abstract : Objective: To investigate the correlation between the features of basement membranes (BMs) of residual myofibers in the sternocleidomastoid muscle (SCM) and fibrosis of congenital muscular torticollis (CMT) in children, and to evaluate the relationship between BM changes and appearance of CMT. Materials and Methods: We reviewed the CMT patients from 2017 to 2018 and performed pathological studies. Forty resected specimens were stained by hematoxylin and eosin and Masson collagen staining. Immunohistochemical staining of collagen IV and laminin was also performed. Five adductor muscle specimens from patients with developmental dysplasia of the hip were used as the control group. Results: Hematoxylin and eosin staining revealed apparent interstitial fibrosis around residual myofibers in lesion specimens. However, the severity of fibrosis differed within the same samples. The average percent area of fibrous tissue in affected SCMs and controls were different significantly. Immunohistochemical staining of collagen IV and laminin showed these proteins were mostly expressed in the BM and vascular wall of affected SCM. However, BMs and myofibers from three different areas within the same SCM tissue exhibited significant differences in proteins expression. Conclusions: Therefore, the defective BMs are associated with myofiber and mesenchyme fibrosis in patients with CMT, which is crucial for understanding the histopathology of SCM.